Evaluation of Diaphragmatic Ultrasound Indices as Predictors of Successful Liberation From Mechanical Ventilation in Subjects With Abdominal Sepsis - Eltrabili, Haytham H; Hasanin, Ahmed M; Soliman, Mahmoud S; Lotfy, Ahmed M; Hamimy, Walid I; Mukhtar, Ahmed M (Respiratory care, 2019)
Sepsis-induced diaphragmatic dysfunction is one of the main risk factors of failure to liberate patients from mechanical ventilation. Several studies addressed diaphragmatic ultrasound as a valuable tool in the assessment of diaphragmatic function during liberation from mechanical ventilation in different populations. However, none of these studies examined the use of diaphragmatic ultrasound to predict failure of liberation from mechanical ventilation in subjects with sepsis METHODS: A prospective observational study was done with subjects on mechanical ventilation and with abdominal sepsis. The diaphragmatic thickening fraction, diaphragmatic excursion, and rapid shallow breathing index were assessed 30 min after a spontaneous breathing trial RESULTS: Thirty subjects were enrolled in the study. Seventeen subjects were successfully extubated (56.6%), whereas extubation failed in 13 subjects (43.4%). The time to the first liberation attempt was significantly shorter in the liberation-success group 2.3 (0.7) d compared with the liberation-failure group 5.8 (4.7) d; = .02. The optimum cutoff value of diaphragmatic thickening fraction for predicting liberation success was ≥30.7%, with a sensitivity of 94.1% and a specificity of 100%. The area under the curve was 0.977. Although diaphragmatic excursion of ≥10.4 mm had a sensitivity of 94% and a specificity of 85% for predicting liberation success, with an area under the curve of 0.85. A rapid shallow breathing index of ≤44 had a specificity of 100% and a sensitivity of 76%; the area under the curve was 0.9. Diaphragmatic ultrasound indices, namely diaphragmatic thickening fraction and diaphragmatic excursion, could be useful parameters for assessment of success of liberation in patients on mechanical ventilation with abdominal sepsis. (ClinicalTrials.gov registration NCT03094299.).